2003
DOI: 10.1111/1471-6402.00103
|View full text |Cite
|
Sign up to set email alerts
|

Calling it Rape: Differences in Experiences of Women Who do or do not Label their Sexual Assault as Rape

Abstract: Past research had found that one-half or more of all women who have had an experience that might meet the definition of rape do not label themselves rape victims. The present study examined the actual rape experiences of 33 women who labeled their assault experience as rape and 56 women who did not label their assault experience as rape through questionnaires and open-ended descriptions of what happened during their assault. Quantitative findings replicated past research, finding that acknowledged victims, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
188
5
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(219 citation statements)
references
References 26 publications
20
188
5
6
Order By: Relevance
“…Rape acknowledgement-or the recognition of an individual's own victimization as a rape-may be influenced by several factors, including the victim's personal rape script and rape-related beliefs, the nature of the assault, reactions received from the victim's close friends and family, and the sociocultural context in which the rape occurred (Bondurant, 2001;Orchowski, Untied, & Gidycz, 2013). Not surprisingly, stereotypical rape characteristics (i.e., stranger perpetrator, perpetrator use of force, victim use of resistance) are associated with greater rape acknowledgment (Hammond & Calhoun, 2007;Kahn, Mathie, & Torgler, 1994;Kahn, Jackson, Kully, Badger, & Halvorsen, 2003;Layman, Gidycz, & Lynn, 1996), although there are some inconsistencies with respect to perpetrator identity (cf. Bondurant, 2001;Layman et al, 1996).…”
Section: Labeling Sexual Violencementioning
confidence: 99%
“…Rape acknowledgement-or the recognition of an individual's own victimization as a rape-may be influenced by several factors, including the victim's personal rape script and rape-related beliefs, the nature of the assault, reactions received from the victim's close friends and family, and the sociocultural context in which the rape occurred (Bondurant, 2001;Orchowski, Untied, & Gidycz, 2013). Not surprisingly, stereotypical rape characteristics (i.e., stranger perpetrator, perpetrator use of force, victim use of resistance) are associated with greater rape acknowledgment (Hammond & Calhoun, 2007;Kahn, Mathie, & Torgler, 1994;Kahn, Jackson, Kully, Badger, & Halvorsen, 2003;Layman, Gidycz, & Lynn, 1996), although there are some inconsistencies with respect to perpetrator identity (cf. Bondurant, 2001;Layman et al, 1996).…”
Section: Labeling Sexual Violencementioning
confidence: 99%
“…Numerous studies have found that the closer an incident is to this script, the more likely it is to be labeled as rape. For example, women are more likely to label the incident as rape if the perpetrator was a stranger or barely known acquaintance (Kahn, Jackson, Kully, Badger, & Halvorsen, 2003;Koss et al, 1988), if it involved physical force, if they resisted physically, if a weapon was used, or if they sustained an injury (Bondurant, 2001;Fisher et al, 2003;Kahn & Mathie, 2000;Layman et al, 1996;Littleton et al, 2009;McMullin & White, 2006). Conversely, women are less likely to label the incident as ''rape'' if it was perpetrated by a romantic partner (Kahn et al, 2003) or if they had been under the influence of alcohol during the experience (Botta & Pingree, 1997;Layman et al, 1996).…”
Section: Factors Associated With Labeling Incidents As Rapementioning
confidence: 99%
“…Um estudo internacional recente (Krahn, 2004) parece ser demonstrativo desta mudança, na medida em que, quando foi pedido às participantes para descreverem uma experiência sexual coerciva recente, se verificou que relatavam, frequentemente, uma violação perpetrada por um namorado ou conhecido. Além disso, quando se questionou se essas situações correspondiam a uma "verdadeira" violação, a maioria concordou, apenas discordando quanto ao facto de o sexo oral ou "digital" constituírem violação -o que mostra que muitas outras mudanças cognitivas precisam ainda de ocorrer.…”
Section: Fundamentação Teóricaunclassified